KONTRIBUSI PEREMPUAN DALAM PENGEMBANGAN PARIWISATA BERBASIS BATIK SEBAGAI MEDIA EDUKASI BUDAYA LOKAL - Meidyna Adjeng Wulandari Wulandari; Praja Firdaus N (Journal Publicuho, 2025)
This study explores the contribution of women in developing culturally educational tourism through batik at Kampung Batik Okra, Surabaya. The women in this community are not only involved as batik artisans, but also act as cultural agents who transmit local values to visitors through educational activities. Their roles are evident in workshops, storytelling about historical and symbolic meanings of batik motifs, and through accessible, interactive communication. using a qualitative phenomenological approach, the research collected data through in-depth interviews, participatory observation, and documentation of cultural symbols. The analysis was conducted interpretively to understand how women give meaning to their roles as cultural narrators. The findings reveal that the women at Kampung Batik Okra play a strategic role in sustaining tradition through education. They teach values such as patience, perseverance, and cultural appreciation through the batik-making process. Although challenges exist, particularly regarding the high cost of hand-drawn batik compared to mass-produced alternatives, the women respond with an educational strategy that builds public appreciation and encourages cultural regeneration, especially among younger generations. This form of educational tourism not only promotes batik as a product, but also reinforces local identity in a participatory and sustainable way.